Total Laparoscopic Hysterectomy Using the Harmonic Scalpel - Winter, Marc L. (Society of Laparoendoscopic Surgeons, 1999)
Total laparoscopic hysterectomy (TLH) is the complete hysterectomy including transection of the uterine vessels and opening/closure of the vaginal vault performed laparoscopically. This procedure can be performed as an alternative to total abdominal hysterectomy in many cases. We previously found use of the harmonic scalpel to be extremely helpful in performing laparoscopically assisted vaginal hysterectomies. In this series, the harmonic scalpel was used to facilitate performing TLH. Our experience has shown this can be performed without major complications in a cost-effective manner.